THE DEVELOPMENT STRATEGY OF NEW UZBEKISTAN IS THE BASIS FOR REFORMS TO INCREASE HUMAN DEGREE AND IMPROVE SPIRITUAL CAPACITY IN OUR COUNTRY (Scientific journal of the Fergana State University, 2025)
This article discusses the meaning and essence of the “New Uzbekistan Development Strategy” and emphasizes its historical significance, which is manifested at three levels. The first is the significance of the “New Uzbekistan Development Strategy” at the national level. The second is the significance of the “New Uzbekistan Development Strategy” at the regional level. The third is the significance of the “New Uzbekistan Development Strategy” at the international (global) level. The priority areas and most important tasks set out in the Development Strategy are analyzed in detail, and a completely new national legal system has been formed in our country. That is, the principle that “A person, his rights, freedoms, especially his dignity are the highest value” is recognized is analyzed.